PENGARUH KEMAMPUAN MEMBACA, KEMAMPUAN BERFIKIR KRITIS DAN KEDISPLINAN BELAJAR TERHADAP KEMANDIRIAN BELAJAR SISWA SMPN 3 PERBAUNGAN - Muhammad Restu Fauzi (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to determine (1) the relationship of reading ability tostudent learning independence (2) the relationship of the ability to thinkcritically towards the independence of student learning (3) the disciplineof learning to the independence of student learning (4) the influence ofreading skills, and the ability to think critically, and towards Studentlearning independence (5) Effect of reading ability, and learning disciplineon student learning independence (6) Effect of critical thinking skills, andlearning discipline on student learning independence (7) Effect of readingability, critical thinking skills, and learning discipline on student learningindependence.The results of the study: 1) There is a Positive andSignificant Relationship in the Ability to Read Against LearningIndependence Students who proved the correlation is worth 0.761. 2)There is a Positive and Significant Relationship to the Critical ThinkingAbility of Students' Learning Independence which is worth 0.883. 3) Thereis a Positive and Significant Relationship in Learning Discipline AgainstStudent Learning Independence, with a value of 0.938 Multiple linearregression obtained by regression equation, Y = 15.238 + 0.352X1 +0.623X2 + e. 5) There is a positive and significant influence betweenreading ability (X1), and learning discipline (X3) on student learningindependence (Y), the results of the calculation of multiple linearregression analysis obtained regression equation that is Y = 12.865 +0.224X1 + 0.720X2 + e . 6) There is a Positive and Significant InfluenceBetween Critical Thinking Ability (X2) and Learning Discipline (X3) onStudent Learning Independence (Y). Multiple linear regression analysisobtained regression equation, namely Y = 15.671+ 0.312X1 + 0.594X2 + e.7) There is a Positive and Significant Influence Between Reading Ability(X1), Critical Thinking Ability (X2) and Learning Discipline (X3) AgainstStudent Learning Independence (Y) which is proven through the results ofthe calculation of multiple linear regression analysis obtained theregression equation that is Y = 11.302 + 0.173X1 + 0, 276X2 + 0.524X3 + e. Results of hypothesis analysis Simultaneously, fcount> ftabel where 237.611> 2.77. And the results of the analysis of the coefficient of determination in this study is the R Square value of 0.963. And with asignificance level of 5%.